CXCL12 and CXCR7 are relevant targets to reverse cell adhesion‐mediated drug resistance in multiple myeloma. (2nd July 2017) - Waldschmidt, Johannes M.; Simon, Anna; Wider, Dagmar; Müller, Stefan J.; Follo, Marie; Ihorst, Gabriele; Decker, Sarah; Lorenz, Joschka; Chatterjee, Manik; Azab, Abdel K.; Duyster, Justus; Wäsch, Ralph; et al.
Summary: Cell adhesion‐mediated drug resistance (CAM‐DR) by the bone marrow (BM) is fundamental to multiple myeloma (MM) propagation and survival. Targeting BM protection to increase the efficacy of current anti‐myeloma treatment has not been extensively pursued. To extend the understanding of CAM‐DR, we hypothesized that the cytotoxic effects of novel anti‐myeloma agents may be abrogated by the presence of BM stroma cells (BMSCs) and restored by addition of the CXCL12 antagonist NOX‐A12 or the CXCR4 inhibitor plerixafor. Following this hypothesis, we evaluated different anti‐myeloma agents alone, with BMSCs and when combined with plerixafor or NOX‐A12. We verified CXCR4, CD49d (also termed ITGA4) and CD44 as essential mediators of BM adhesion on MM cells. Additionally, we show that CXCR7, the second receptor of stromal‐derived‐factor‐1 (CXCL12), is highly expressed in active MM. Co‐culture proved that co‐treatment with plerixafor or NOX‐A12, the latter inhibiting CXCR4 and CXCR7, functionally interfered with MM chemotaxis to the BM. This led to the resensitization of MM cells to the anti‐myeloma agents vorinostat and pomalidomide and both proteasome inhibitors bortezomib and carfilzomib. Within a multicentre phase I/II study, NOX‐A12 was tested in combination with bortezomib‐dexamethasone, underlining the feasibility of NOX‐A12 as an active add‐on agent to antagonize myeloma CAM‐DR.